User Force-Dependent Variable Impedance Control in Human-Robot Interaction - Muller, Florian; Janetzky, Jan; Behrnd, Uwe; Jakel, Jens; Thomas, Ulrike (IEEE International Conference on Automation Science and Engineering (CASE), 2018)
In this paper a novel type of variable impedance control (VIC) is presented. The controller adjusts the impedance depending on the force input of the user. In this way it is easy to accelerate and decelerate. Additionally, for high velocity the damping decreases and vice versa. This approach could be interpreted as a combination of acceleration-dependent VIC and velocity-dependent VIC. To guarantee stability, a stability observer is introduced. The observer is based on a model which describes a combined passive and active behavior of the user. In addition, we present a user study with 45 participants where the differences between VIC, VIC with stability observer and a pure admittance controller were investigated. The results show an improvement of the VIC with stability observer in relation to the pure admittance controller among different categories. With both the variable impedance controller and the variable impedance controller with stability observer, the participants significantly improved their times in comparison to the pure admittance controller, while they maintained the same level of precision. Also the workload was considerably smaller and the user comfort increased with both controllers compared to the usage of the pure admittance controller.